(untitled) (ASEAN Engineering Journal, 2024)
Blockchain deployments require efficient consensus models in order to be scaled for larger networks. Existing consensus models either use stake-levels, trust-levels, authority-levels, etc. or their combinations in order to reduce mining delay while maintaining higher security levels. But these models either have higher energy requirements, lower security, or have linear/exponential relationship between mining delay and length of the chains. Due to these restrictions, the applicability of these models is affected when deployed under real-time network scenarios. To overcome these issues, this text proposes design of an efficient novel trust-based hybrid consensus model for securing blockchain deployments. The proposed model initially uses a hybrid consensus model that fuses Proof-of-Work (PoW), Proof-of-Stake (PoS) with Proof-of-Temporal-Trust (PoTT) for improving security while maintaining higher Quality of Service (QoS) levels. The PoTT Model fuses together temporal mining delay, temporal mining energy, throughput and block mining efficiency in order to generate miner-level trusts. These trust values are fused with Work efficiency and Stake levels and used for selection of miners. The selected miners are used for serving block addition requests, which assists in improving mining speed by 3.2%, reducing energy consumption 4.5%, and improving throughput by 8.5%, while improving block mining efficiency by 2.9% when compared with existing mining optimization models. This performance was validated under Sybil, Finney, Man-in-the-Middle, and Spoofing attacks. Performance of the model was observed to be consistent even under attacks, thereby making it useful for real-time network scenarios.